Analisis Keterkaitan Stres Akademik dengan Kenakalan Remaja Pendekatan Solutif Melalui Pendidikan Karakter - dewi, yulia; Wariyati; Muthia Aprilianty , Nabila Hana Ariqah , Widya Wahyuni Br. Silalahi ,Nazwa Aulia Syahrani. (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study connects two major problems in education: adolescent misbehavior and academic pressure. Research on the implementation of character education shows that cooperation between teachers and parents is crucial in reducing adolescent misbehavior by instilling effective character values. On the other hand, studies on academic pressure reveal students' subjective views of academic demands as a cause of negative physical, behavioral, and emotional reactions that affect mental health and academic achievement. Although different in focus, these two problems are interconnected, where academic pressure can contribute to adolescent misbehavior. Further research is needed to investigate the causal relationship between academic pressure and adolescent misbehavior, and to assess the effectiveness of character education as a solution to address both problems.